Usability Testing On Inventory Application Using Performance Measurement, Retrospective Think Aloud, And System Usability Scale Technique. - Dewi, Gusti Ayu Putu Achintya; Dantes, Prof. Dr. Gede Rasben; Divayana, Prof. Dr. Dewa Gede Hendra (Information Technology and Science (ITScience), 2023)
System evaluation is carried out with the aim of knowing system weaknesses that hinder users from implementing them. Inventory application users in Badung Regency, based on interviews conducted, had never been evaluated and there were several records collected regarding complaints from users. This study aims to evaluate the value of the success and speed of doing tasks with Performance Measurement, RTA and SUS Techniques. Based on the results of processing the data obtained with the performance measurement technique, it shows that pages are generally quite effective because they function properly, even though there was an error in one of the tests in carrying out the task by the respondent. This is due to a period mismatch caused by the user's own error, namely forgetting to change the period. Efficiency when viewed from the results of the data obtained with performance measurement techniques, it is generally known that inventory applications are quite efficient. For user satisfaction, the score for the respondent's questionnaire is 61.18 which is obtained, this means that the score is smaller than the SUS standard score, which is 68. So it can be said that respondents are not satisfied using the Inventory Application. The results obtained from the usability testing process show that the Inventory Application page which is the object of research still does not meet the criteria for a product with good usability. This can be seen in the assessment of the level of effectiveness, efficiency, and user satisfaction. This inventory application is not able to meet the good criteria for these three aspects.